The effect of training some planning approaches in developing some special physical abilities and basic skills for soccer players for the second professional clubs / Tunisia - Al-Amiri, Diaa al-Din (sports creativity, 2025)
The research consisted of five chapters, the first of which included an introduction and the importance of the research, addressing the importance of training tactical approaches in developing players' specific abilities, given their important and influential role in raising their levels, developing their specific technical and physical abilities, and improving their performance. The research problem was manifested in the weakness of their technical and physical performance as a result of random and unorganized training of players in the second division clubs in Tunisia (Al-Akabar). The research aimed to: - Prepare tactical approach training for the research sample in Tunisia. - Identify these training exercises in Tunisia. The researcher assumed the following: - There are statistically significant differences between the pre- and post-tests in favor of the experimental group. - Statistically significant differences between the post-tests in favor of the experimental group. The research subjects were players from the Ariana Sports Association participating in the 2018-2019 league championship. The research period extended from May 14, 2018, to July 16, 2019. The sample test was conducted at the Ariana Sports Stadium. The second chapter included theoretical studies that covered strategic approaches, and specific physical abilities. The third chapter included research procedures in terms of research methodology, research tools, exploratory experiments, and statistical methods. It also included the application mechanism for the training program for tactical approaches. The fourth chapter included a presentation, analysis, and discussion of the research results, through which the researcher was able to achieve the research objectives and hypotheses. The fifth chapter contained the conclusions and recommendations made by the researcher, in which he recommended emphasizing the training of the strategic approaches he developed and recommended through emphasizing the training of strategic approaches in the